Research on acquisition method of MBOC/Sideband AltBOC signals - Deng Zhong-liang; Yin Lu; Xi Yue; Zhan Zhong-wei; Dong Hui; Wang Guan-yi (Institute of Advanced Engineering and Science, 2014)
New GNSS signal systems (MBOC/AltBOC) are different from traditional one (BPSK). Acquisition method of new signal systems need to be studied to adapt the new modulation scheme. On the other hand, there are more acquisition cells and long stop time on each cell because of the features of the new GNSS signal systems. So the average acquisition time of the new signals increase much longer than the former one. The new signal features was analyzed at first in this paper, and then the acquisition algorithm of QPSK and MBOC modulated signals was introduced separately. At last, a Multiplexing Channel of Time-Division technique and Multi-frequency aid algorithm was proposed to increase the acquisition speed. This new fast acquisition algorithm significantly reduced the average acquisition time of the new GNSS signal systems. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4485